Effect of the Addition of Dispersed Reinforcement on the Resilient Modulus of Slightly Cemented Non-Cohesive Soil - Wasil Mariola; Dobrzycki Patryk; Zabielska-Adamska Katarzyna (Studia Geotechnica et Mechanica, 2023)
The aim of this article is to determine the effect of the addition of dispersed reinforcement on the resilient modulus of non-cohesive soil used as material for improved subgrade or subbase course of the pavement structure. Resilient modulus (Mr) is a parameter used in road construction, which characterises soil subgrade or base aggregates stiffness in flexible pavement subjected to the traffic load. This article presents laboratory test results of non-cohesive coarse material (gravelly sand – grSa – without fines) with the addition of 1.5% cement and dispersed reinforcement – polypropylene fibres in lengths of 12, 18 and 40 mm. Tests were conducted on the samples with various percentages of fibres (0, 0.2 and 0.3%) relating to the dry mass of the soil. Samples were compacted according to the standard Proctor (SP) and modified Proctor (MP) methods. Main laboratory tests were conducted in the triaxial apparatus enabling testing samples subjected to cyclic loads according to AASHTO T307 standard. Resilient modulus was determined after 7 and 28 days of curing. The results indicate the influence of fibre amount, fibre length, and curing time on the Mr of the soil modified with 1.5% of cement. The obtained results were also influenced by the method of compaction. The addition of polypropylene fibres decreases the resilient modulus of soil stabilised by 1.5% of cement. The best results of dispersive reinforcement were obtained for samples containing 0.3% of fibres with a length of 18 mm, compacted by the MP methods.